Pleomorphic hyalinizing angiectatic tumor revisited: all tumors manifest typical morphologic features of myxoinflammatory fibroblastic sarcoma, further suggesting 2 morphologic variants of a single entity. - Michal, Michael; Kazakov, Dmitry V.; Hadravsky, Ladislav; Agaimy, Abbas; Svajdler, Marian; Kuroda, Naoto; Michal, Michal (Annals of Diagnostic Pathology, 2016)
We describe 9 cases of pleomorphic hyalinizing angiectatic tumor (PHAT). Recently described TGFBR3 and MGEA5 gene rearrangements in these tumors have confirmed the long-hypothesized link between PHAT and another soft tissue entity, the myxoinflammatory fibroblastic sarcoma (MIFS). Myxoinflammatory fibroblastic sarcoma and PHAT share the same translocation and in addition have a very similar clinical presentation. However, to our best knowledge, no study has ever addressed the striking morphologic similarities between MIFS and PHAT. Our findings based on histological criteria suggest that most, if not all, tumors diagnosed as PHAT might, in fact, represent examples of MIFS that, in addition to a conventional MIFS morphology, manifest aberrant angiectatic hyalinized vessels.
EVALuna2:6757